The Use of Some Growing Media and Shading Level to Increase the Growth of Litsea cubeba's Seedling - Yetti Heryati; Retno Agustarini (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Kilemo (Litsea cubeba L. Persoon) is one of the potential economic producing essential oils, because all body part of kilemo’s trees can produce essential oil. The development of kilemo is constrained by the lack of information on cultivation technology. Research on kilemo nursery has been carried out, however the information was not completely provided especially those related to shading and media. Therefore the purpose of the study is to get information on the response of kilemo seedlings on the use of shade and media in the nursery. The study was conducted in a Greenhouse of Forest Tree Seed Technology Research & Development Center (FTSTRDC) Bogor. The experiment used Completely Randomized Design with Factorial Pattern, consisted of 2 factors and 10 replications. The first factor is media consisting of 5 types of media: soil; compost charcoal;soil + compost charcoal 3:1 (v/v); soil + paddy husk charcoal 3:1 (v/v); and soil + charcoal compost + paddy husk charcoal 3: 1: 1 (v/v/v). The second factor is shade consisting of 4 shade intensity that is: 0 percent, 25 percent, 50 percent, 75 percent. The results showed that Media of soil + paddy husk charcoal 3:1 (v:v) with shade 25 percent gives the best growth to Litsea cubeba’s seedlings 5 months after weaning on the parameters of height (12.64 cm), number of leaves (5.56), dry weight (0.182), seed quality index (0.021) and TR ratio (1.967).